Gênero e violência: relação entre masculinidades e práticas de violências contra a mulher - Pinto, Nilberto dos Santos (2023)
The theme involving gender, violence and masculinities is very complex, presenting different dynamics that affect the construction of interpersonal relationships in society. From a restricted view about masculinities, under the aegis of structural machismo, men, to be recognized as such, need to demonstrate certain characteristics, such as virility, aggressiveness and violent behavior. Thus, women often end up being the main victims in this process. In this sense, the following starting question emerges: What is the relationship between masculinities and practices of violence against women? Therefore, taking into consideration the general objective of the research, which was to understand the impacts of masculinities on the practices of violence against women, the following specific objectives were established: To verify men's views on what is considered violence against women, To identify which masculinities men recognize themselves with in their relationships with women and To analyze men's views on violence against women based on their experiences in the reflection groups. The study, which is characterized as qualitative, was divided into two parts. First, the researcher participated in three reflection groups of men reported for violence against women. Next, three interviews were conducted with men, who were chosen because they were participants or had already participated in the reflective groups. Thus, the study approached 32 participants in total, 29 men in the reflective groups with the observation process and 3 men in the semistructured interviews. The data analysis was carried out by means of content analysis, using the description and interpretation of the material from the field diaries and interviews, with the support of the Atlas TI qualitative analysis software. It was concluded that men's view of violence against women was very restricted, focused only on physical violence, represented by the act of hitting to leave marks, disregarding the other forms of violence. It was also concluded that men recognized themselves from a masculinity10 intrinsically charged by structural machismo, with discourses focused on male superiority and domination over women. Finally, analyzing the vision of men from their experience in the reflection groups, we conclude that, as much as they arrived with a macho and restricted vision of violence against women, the men changed as they participated in the reflection groups. So as they participated in the groups, they became more aware, learned, and changed their behaviors. In summary, this research allowed a critical analysis of the theme, contributing to encourage new reflections with a view to enabling greater gender equity.